Steps and Procedures to teach Writing Skill via "wiki" Program among Arabic Learners, Arabic as a Second Language as a Case Study - Nurkhamimi Zainuddin; Muhammad Sabri Sahrir; Mohd Feham Md. Ghalib (International Islamic University Malaysia, 2024)
This paper discusses the learning process of writing skills among the students of the Center of Foundational Studies, International Islamic University Malaysia from the theoretical and applied aspects. The learning problems and the foundations of the suitable teaching method and its design will also be discussed. Subsequently, the steps in learning this skill from the online program in the internet called “wiki” are presented. The effect of taking up this program is studied by using the writing standards list as provided in the program itself. The analysis proved that it did manage to contribute to improve the learning abilities of the students and develop their thinking creativities